HERMANN WILHELM ABICH IM KAUKASUS: ZUM ZWEIHUNDERTSTEN GEBURTSTAG - Seibold I.; Seibold E. (My University, 2006)
Hermann Abich was born in 1806 in Berlin and died in 1886 in Graz. He grew up in a wealthy family which had friendly relations with famous scientists like Alexander von Humboldt, Leopold von Buch or Carl Ritter. After his studies in Heidelberg and Berlin he turned to extended fieldwork at the volcanoes of Italy. In 1833–1834 he published excellent petrological/chemical results and got soon a good scientific reputation. Thus he was nominated as Professor for Geology and Mineralogy of the prestigious Russian University in Dorpat (now Tartu, Esthonia) in 1842. In 1844 he was sent to Armenia by the Russian authorities. For the next three decades his fieldwork with about 190 publications was concentrated on the Great and Lesser Caucasus. This was a period of Russian expansion to the South with long-lasting regional fights. But he enjoyed the support of powerful governors. He was an indefatigable and enthusiastic explorer and a precise observer and designer. His interests covered many fields: morphology, glaciology, structural geology, volcanology with Thermal Springs, mineral resources from hydrocarbons, coal, salt to ores, stratigraphy and paleontology as a base for geological maps. But he also gave advice for practical problems, and he was active in meteorology, botany and archaeology. Alltogether he became “the Father of Caucasus Geology”. The following sketch stresses only on three aspects of his activities. He was one of the first pioneers in hydrocarbon exploration, especially around the anticlines with the mud volcanoes near Baku. In many respects, however, his fundamental ideas were erronous. He explained the structure of the Great Caucasus by the traditional theories of Leopold von Buch and Elie de Beaumont. The Caucasus anticline “was elevated by forces acting from beneath”. Following them he tried to discover regularities in the strike of mountain chains. Similarily he treated volcanism like Alexander von Humboldt and Leopold von Buch with their two groups of phenomena: voluminous, mostly basaltic “elevation craters” versus isolated, mostly trachytic and relatively small cones of “true volcanoes”. In spite of the isolation of the Caucasus region he had cultivated continuously contacts with leading geologists in Europe and was honoured by many institutions. He left Russia in 1876 for Vienna planning to write there the final monograph volumes about his investigations but he died before he could complete them.
Keywords: HERMANN ABICH; KAUKASUS: HISTORICAL FRAME OF EXPLORATION; GEOLOGY; EARLY PETROLEUM GEOLOGY